Overview of Dengue Hemorrhagic Fever in Kebayoran Lama - Rojali, Rojali; Rstiaty, Indah; Syafitri, Dini; Maghfiroh, Asyfi (Jurnal Kesehatan, 2023)
Dengue Hemorrhagic Fever is a vector-based disease still a significant problem in Indonesia. For two years, the Kebayoran Lama Selatan Sub-District has been in the first position of cases in the Kebayoran Lama District. This study aims to find out the distribution of dengue incidence based on individual characteristics (age, sex, education, knowledge, attitudes) and environmental factors (presence of mosquito larvae, water reservoirs (TPA), lighting, humidity, presence of wire netting, and presence of larvae-eating fish. This research is descriptive with a research design case study in June 2022. The population was DHF sufferers in 2020-2021. The sampling technique uses the technique of total sampling. Data collection was carried out through interviews, observation, and direct measurements. The results were 52.6% of patients with female sex, 52.6% of patients with an age range â‰¥15, 36.8% of patients with elementary school education, 73.7% had a good level of knowledge, 78.9% had a good attitude, 52.6% found mosquito larvae, 89.5% did not close the water reservoir, 57.9% did not have wire mesh in the ventilation, 100% did not have larvae-eating fish, 52.6% lighting did not meet the requirements, and 100% humidity did not meet the criteria. Based on the results of the study, it is recommended to routinely drain the TPA once a week, close the TPA both inside and outside the house, install wire mesh on the ventilation, use a humidifier to regulate humidity, install glass tiles, and maintain environmental cleanliness as a form of prevention of DHF.